2009
DOI: 10.12693/aphyspola.116.s-142
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Formation of Novel Nanomaterials: Synthesis and Cathodoluminescence of Silicon Carbide Nanowires

Abstract: This paper presents the combustion synthesis and characterization of one-dimensional silicon carbide nanostructures (nanowires of 3C-SiC polytype with zincblend structure) by means of cathodoluminescence technique. Cathodoluminescence spectra of nano-SiC samples and, as a reference, of a commercially available SiC micropowder are compared. It is shown that the emission band at 1.97 eV which is slightly evidenced in the spectrum of the commercial SiC under 10 keV electron beam irradiation becomes the prevailing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In the present paper we continue our recent efforts on synthesis and characterization of novel SiC 1D nanostructures, namely, obtained in the form of nanowires [2,3] and report their infrared spectroscopic characterization in the medium infrared domain at 20 and 300 K.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In the present paper we continue our recent efforts on synthesis and characterization of novel SiC 1D nanostructures, namely, obtained in the form of nanowires [2,3] and report their infrared spectroscopic characterization in the medium infrared domain at 20 and 300 K.…”
Section: Introductionmentioning
confidence: 81%
“…Structural studies have indicated that the obtained modification of SiC is 3C polytype with cubic unit cell. More details about morphology of the obtained SiC nanowires can be found in [2,3].…”
Section: Methodsmentioning
confidence: 99%
“…The luminescence spectra were recorded in the energy range of 1.0-5.0 eV at room temperature (RT) and liquid nitrogen temperature (LNT). This experimental set-up is an unique tool for the in-situ investigations of the electronic structure of wide band gap materials as well as of nanocrystalline semiconductors [21][22][23][24][25].…”
Section: Measurementsmentioning
confidence: 99%